Worker Protection Standard: Additional Requirements for Agricultural Employers of Workers - Frederick M. Fishel (EDIS, 2017)
In 1992, the US Environmental Protection Agency (EPA) issued a comprehensive regulation called the Worker Protection Standard for Agricultural Pesticides (WPS). This regulation is primarily intended to reduce the risks of illness or injury to workers and handlers resulting from occupational exposures to pesticides used in the production of agricultural plants on agricultural establishments (i.e., farms, forests, nurseries and enclosed space production facilities, such as greenhouses). The WPS requires agricultural employers to take steps to reduce pesticide-related risks when agricultural workers and pesticide handlers are exposed to these pesticides. The EPA has made several changes to the WPS since it was fully implemented in 1995. On November 2, 2015, the EPA revised the WPS, making significant changes to the rule’s requirements. Most of the revised provisions will become effective January 2, 2017; there are four provisions that are delayed until January 2, 2018. In late 2016, the EPA released the revised “How to Comply Manual” to provide an updated resource. The entire document is posted on their website at https://www.epa.gov/sites/production/files/2016-09/documents/htcmanual_final.pdf. This document will address the additional requirements for agricultural employers of workers under the revised WPS.